Improving Care And Research Electronic Data Trust Antwerp (iCAREdata): a research database of linked data on out-of-hours primary care. (December 2016) - Colliers, Annelies; Bartholomeeusen, Stefaan; Remmen, Roy; Coenen, Samuel; Michiels, Barbara; Bastiaens, Hilde; Van Royen, Paul; Verhoeven, Veronique; Holmgren, Philip; De Ruyck, Bernard; Philips, Hilde
Abstract Background Primary out-of-hours care is developing throughout Europe. High-quality databases with linked data from primary health services can help to improve research and future health services. Methods In 2014, a central clinical research database infrastructure was established (iCAREdata: Improving Care And Research Electronic Data Trust Antwerp, www.icaredata.eu ) for primary and interdisciplinary health care at the University of Antwerp, linking data from General Practice Cooperatives, Emergency Departments and Pharmacies during out-of-hours care. Medical data are pseudonymised using the services of a Trusted Third Party, which encodes private information about patients and physicians before data is sent to iCAREdata. Results iCAREdata provides many new research opportunities in the fields of clinical epidemiology, health care management and quality of care. A key aspect will be to ensure the quality of data registration by all health care providers. Conclusions This article describes the establishment of a research database and the possibilities of linking data from different primary out-of-hours care providers, with the potential to help to improve research and the quality of health care services.